Copper Doped Zeolitic Imidazole Frameworks (ZIF-8): A New Generation of Single-Atom Catalyst for Oxygen Reduction Reaction in Alkaline Media. Issue 15 (6th August 2020) - Parkash, Anand
Abstract : Reasonable design of electrocatalyst based on abundant earth elements is of great importance for sustainable energy use. Transition metal nitrogen doped carbon (TM-N/C) materials demonstrate excellent catalytic activity. However, there is still a lack of comprehensive understanding of these TM-N/C-systems. Herein, we have developed an effective approach to develop highly active and stable Cu promoted N-doped carbon (Cu-N/C) catalysts. The impacts of copper doping and temperature of pyrolysis on catalytic performance have been studied. The Cu-NC-800 catalysts exhibited excellent catalytic activity and stability with an onset potential (Eo ) of 0.99 V and half-wave potential (E1/2 ) of 0.85 V. It also shows strong the long-term stability. The synergistic effect between Cu (II)-N ligand and Cu 0 nanoparticles is high, the active center is small, the transfer of mass is rapid, and the electrocatalytic efficiency is increased. The findings showed that the non-noble metal-based catalyst's bifunctional oxygen electrode activities prepared in this study were as high as those of commercial oxygen-based, noble metal catalysts.